Demographic Profiles and Sources of Infection among Septic Patients admitted at ICU of a Public Hospital in Dhaka City - Sarker, Subroto Kumar; Azam, Mohammod Saiful; Mondal, Montosh Kumar; Goswami, Uday Kumar; Mohammad Mohsin, - (Bangladesh Journal of Infectious Diseases, 2021)
Background: Sepsis occurs due to different sources of infection. Objective: The purpose of the present study was to see the demographic profiles and sources of infection among septic patients admitted at ICU of a public hospital in Dhaka City. Methodology: This descriptive cross sectional study was conducted in the Intensive Care Unit of the department of Anaesthesia Analgesia, Palliative and Intensive Care Medicine, Dhaka Medical College Hospital, Dhaka, Bangladesh over a period of 12 months starting from January 2016 to December 2016. All patients admitted to ICU with the features of severe sepsis and septic shock according to SSC guidelines with the age of more than or equal to 18 years in both sexes were set as selection criteria for this study. Instruments required to perform the study were data sheet addressing the demographic data, primary source of severe sepsis and organ dysfunctions. BSepsis was confirmed by detection of serum lactate and culture of blood. Result: A total number of patients was 69 cases. The mean with SD was 38.72 ±13.43 with the age range of patient 18 to 65 year. The male and female ratio was 1.7:1. The most common source of infection were abdomen which was 30(43.5%) cases followed by CNS, respiratory tract, urogenital tract and GIT which were (21.7%) cases, (14.5%) cases, (17.4%) cases and (2.9%) cases respectively. Among the 69 patient 20 patients were blood cultures positive, 15 patients were pus culture positive, 10 patients were urine/catheter tip culture positive. Conclusion: In conclusion young adult male is most commonly suffering from sepsis in ICU mostly due to infection of abdomen. Bangladesh Journal of Infectious Diseases 2020;7(2):40-43